Polyacetimide magnetic nanoparticles with core-shell structure and preparation method thereof
By coating the SiO2 shell on the oil-soluble magnetic nanoparticles synthesized by the thermal decomposition method and modifying it with polyacetimide, the problem of difficulty in dispersing in water is solved, and its biocompatibility and application potential are improved.
Patent Information
- Application Number
- CN202110845852.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-07-26
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-07-26
AI Technical Summary
In the prior art, oil-soluble magnetic nanoparticles synthesized by thermal decomposition method are difficult to perform effective surface modification, which limits their application in the field of biomedical science.
The SiO2 shell layer is coated on the oil-soluble magnetic nanoparticles synthesized by thermal decomposition and surface modification is used with polyacetimide, which increases the dispersion of the nanoparticles in water.
The good dispersion and biocompatibility of magnetic nanoparticles in water have been achieved, and its application potential in the field of biomedical science has been enhanced.
Smart Images

Figure CN113724952B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to polyacetimide magnetic nanoparticles with a core-shell structure and a preparation method thereof, belonging to the technical field of composite materials. Background Art
[0002] Magnetic nanoparticles are easy to synthesize and surface-modify, have excellent magnetic properties and high specific surface area, and low toxicity. After surface modification, they have a wide range of applications in biomedical fields such as magnetic resonance imaging, tumor diagnosis, biological separation, cell tracing, and construction of multimodal molecular imaging probes. In recent years, many synthesis methods of magnetic nanoparticles have been gradually developed and improved, but directly synthesized magnetic nanoparticles have disadvantages such as poor dispersibility, poor biocompatibility, and easy oxidation, which greatly limits their subsequent applications. For this reason, they are usually surface-modified to improve their performance.
[0003] The commonly used preparation method of magnetic nanoparticles is chemical synthesis method, which mainly includes thermal decomposition method, coprecipitation method, solvothermal method, etc. The magnetic nanoparticles synthesized by coprecipitation method or solvothermal method have the disadvantages of large particle size, poor monodispersity, and poor crystallization effect. The magnetic nanoparticles synthesized by this method have large particle size, and the monodispersity will be worse after surface modification. The magnetic nanoparticles synthesized by thermal decomposition method have the advantages of small particle size, good monodispersity, and high crystallinity. At present, the magnetic nanoparticles synthesized by this method are mostly oil-soluble magnetic nanoparticles, which are difficult to surface modify, which limits their application to a certain extent. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the defects of the prior art and provide an oil-soluble magnetic nanoparticle synthesized by thermal decomposition method, which is coated with a silica shell layer after post-treatment and then surface-modified with polyacetimide. The surface of the magnetic nanoparticle group after surface modification has a large number of amino groups and has good dispersibility in water.
[0005] In order to solve the above technical problems, the present invention provides a polyacetimide magnetic nanoparticle with a core-shell structure, wherein the magnetic nanoparticle has Fe3O4 as a core, SiO2 as a shell, and the shell surface modification material is polyacetimide.
[0006] The present invention provides a method for preparing polyacetimide magnetic nanoparticles with a core-shell structure, comprising:
[0007] Synthesis of oil-soluble magnetic nanoparticles by thermal decomposition;
[0008] The synthesized oil-soluble magnetic nanoparticles are treated with a surfactant to obtain magnetic nanoparticles dispersed in water;
[0009] The surface of the obtained magnetic nanoparticles dispersed in water is coated with a SiO2 shell layer to obtain Fe3O4@SiO2 magnetic nanoparticles dispersed in water;
[0010] An alcohol solution containing poly(acetimide) was added to Fe3O4@SiO2 magnetic nanoparticles to react and obtain Fe3O4@SiO2@PEI magnetic nanoparticles.
[0011] Furthermore, the thermal decomposition method for synthesizing oil-soluble magnetic nanoparticles is specifically as follows: dissolving an iron precursor in a high-boiling point solvent, then adding a high-boiling point reducing agent, removing the low-boiling point solvent at 110-150°C in a nitrogen atmosphere, and then heating to a set temperature and reflux to obtain oil-soluble magnetic nanoparticles.
[0012] Furthermore, the iron precursor is one or more of pentacarbonyl iron, ferrous acetylacetonate, and iron oleate; the high boiling point solvent is one or more of toluene, eicosane, n-octadecane, and octadecene; the high boiling point reducing agent is one or both of oleic acid and oleylamine; the reflux temperature is 220-330° C., the reflux time is 0.5-2h, and the molar ratio of the iron precursor, the high boiling point solvent, and the high boiling point reducing agent is 1:(10-80):(1-9).
[0013] Furthermore, the specific preparation method of the magnetic nanoparticles dispersed in water is: dissolving the prepared oil-soluble magnetic nanoparticles in a polar solvent, adding an aqueous solution of a surfactant with a mass fraction of 0.5%-5%, controlling the temperature between 60-90°C, stirring under a nitrogen atmosphere and blowing dry the polar solvent to obtain magnetic nanoparticles dispersed in water.
[0014] Furthermore, the polar solvent includes one or more of trifluoroacetic acid, dimethyl sulfoxide, N,N-dimethylformamide, pyridine, acetone, tetrahydrofuran, and chloroform; the surfactant aqueous solution is one or more of an aqueous solution of sodium dodecylbenzenesulfonate, an aqueous solution of sodium dodecyl sulfate, and an aqueous solution of Tween; and the mass ratio of the oil-soluble magnetic nanoparticle solution, the polar solvent, and the surfactant aqueous solution is 1: (10-30): (200-400).
[0015] Furthermore, the specific preparation method of the magnetic nanoparticles with a SiO2 shell layer on the surface is: take the magnetic nanoparticles dispersed in water, add ethanol to control the volume of ethanol to be between 8-12 times of water, then add ammonia water to adjust the pH of the system to alkaline, add tetraethyl orthosilicate, react at 0-20°C, wash and disperse in an alcohol solution to obtain an alcohol dispersion of Fe3O4@SiO2 magnetic nanoparticles.
[0016] Furthermore, the alcohol solution includes one or more of methanol, ethanol, n-butanol, and isopropanol, and the volume ratio of the magnetic nanoparticles dispersed in water to tetraethyl orthosilicate is 1:(0.03-0.1).
[0017] Furthermore, the mass fraction of the Fe3O4@SiO2 magnetic nanoparticles dispersed in water is 0.4%-4%, the mass fraction of polyacetimide in the alcohol solution containing polyacetimide is 0.1%-1%, and then an aldehyde solvent with a mass fraction of 1%-10% is added dropwise, refluxed at 60-90°C for 1-4h, and Fe3O4@SiO2@PEI magnetic nanoparticles are obtained after washing.
[0018] Furthermore, the alcohol solution includes one or more of methanol, ethanol, n-butanol, and isopropanol; the aldehydes are one or more of formaldehyde, acetaldehyde, succinaldehyde, and glutaraldehyde; and the volume ratio of the Fe3O4@SiO2 magnetic nanoparticles dispersed in water, the alcohol solution containing polyacetimide, and the aldehyde solvent is 1: (0.1-0.3): (10-30).
[0019] The beneficial effects achieved by the present invention are:
[0020] (1) The present invention coats the surface of magnetic nanoparticles with a layer of SiO2 shell. SiO2, as an excellent inorganic surface modifier of magnetic nanoparticles, has the advantages of improving the biocompatibility, dispersibility, and hydrophilicity of magnetic nanoparticles. And because it has a strong negative charge, it is easy to be further modified by subsequent groups.
[0021] (2) The magnetic nanoparticles prepared by thermal decomposition have the characteristics of good monodispersity and controllable particle size, but are mostly oil-soluble. The present invention can perform surface modification on the oil-soluble magnetic nanoparticles obtained by thermal decomposition. The specific method is to treat the oil-soluble magnetic nanoparticles with a surfactant to change them from hydrophobic to hydrophilic, and then coat the surface with a silica shell. Since the surface of silica has a strong negative charge, polyacetimide can be modified by electrostatic adsorption. The surface of the magnetic nanoparticle group after surface modification has a large number of amino groups and has good dispersibility in water. The preparation method of the present invention is simple, effective and reproducible. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is a transmission electron micrograph of the oil-soluble Fe3O4 magnetic nanoparticles synthesized in Example 1;
[0023] Figure 2 is a particle size distribution diagram of the oil-soluble Fe3O4 magnetic nanoparticles synthesized in Example 1;
[0024] Figure 3is a transmission electron microscope image of the Fe3O4@SiO2 magnetic nanoparticles synthesized in Example 1;
[0025] Figure 4 is a particle size distribution diagram of Fe3O4@SiO2 magnetic nanoparticles synthesized in Example 1;
[0026] Figure 5 is a transmission electron microscopy image of the Fe3O4@SiO2@PEI magnetic nanoparticles synthesized in Example 1;
[0027] Figure 6 This is the particle size distribution diagram of the Fe3O4@SiO2@PEI magnetic nanoparticles synthesized in Example 1. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with the examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention.
[0029] Embodiment 1:
[0030] 1. Preparation of oil-soluble Fe3O4 magnetic nanoparticles by high temperature thermal decomposition
[0031] Take 9.0g of iron oleate solid, add 26.4g of octadecene and 2.1g of oleic acid, stir for half an hour under nitrogen atmosphere, then quickly heat to 330℃ and reflux for 0.5h. Collect the product and wash it with ethanol several times to obtain oil-soluble Fe3O4 magnetic nanoparticles. Figure 1 It is a transmission electron microscope image of the oil-soluble Fe3O4 magnetic nanoparticles synthesized in this example. Figure 2 : is the particle size distribution diagram of the oil-soluble Fe3O4 magnetic nanoparticles synthesized in this example, the particle size is 4.98nm, and the coefficient of variation is 20.35%.
[0032] 2. Improve the dispersibility of Fe3O4 magnetic nanoparticles
[0033] Take 500 mg of the above oil-soluble Fe3O4 magnetic nanoparticles, add 5 mL of tetrahydrofuran, stir to dissolve, and then add 150 mL of sodium dodecyl sulfate aqueous solution (2.5% w / v). After ultrasonic dispersion, mechanical stirring, nitrogen gas is introduced, and the temperature is raised to 60°C. After being exposed for 5 hours, the remaining liquid is collected, centrifuged several times with ethanol and deionized water, and then dispersed in 5 mL of deionized water to obtain a uniformly dispersed aqueous dispersion of Fe3O4 magnetic nanoparticles.
[0034] 3. Coating of Fe3O4 magnetic nanoparticles with silica shell
[0035] Take the Fe3O4 magnetic nanoparticles dispersed in deionized water obtained above, add 250 mL of ethanol and 5 mL of deionized water, stir mechanically in an ice water bath, add ammonia water to adjust the pH value of the system to between 8 and 9, stir for half an hour, add 0.5 mL of tetraethyl orthosilicate, stir for 2 hours, then add another 0.5 mL of tetraethyl orthosilicate, stir at room temperature for 12 hours, collect the resulting product, centrifuge it several times with ethanol and deionized water, and disperse it in 5 mL of methanol to obtain a methanol dispersion of Fe3O4@SiO2 magnetic nanoparticles. Figure 3 It is a transmission electron microscope image of the Fe3O4@SiO2 magnetic nanoparticles synthesized in this example. Figure 4 : is the particle size distribution diagram of the Fe3O4@SiO2 magnetic nanoparticles synthesized in this example, the particle size is 9.74nm, and the coefficient of variation is 9.39%.
[0036] 4. Modification of Fe3O4@SiO2 magnetic nanoparticles surface with polyacetimide
[0037] Take 5 mL of the methanol dispersion of the above-mentioned Fe3O4@SiO2 magnetic nanoparticles, add 25 mL of methanol solution of polyacetimide (3% w / v), heat to 70°C, add 50 mL of methanol solution of formaldehyde (3% w / v), and reflux for 4 hours. The mixture is repeatedly centrifuged and washed with methanol until the upper liquid is colorless and transparent. The liquid is vacuum dried and dispersed in water. Figure 5 It is a transmission electron microscope image of the Fe3O4@SiO2@PEI magnetic nanoparticles synthesized in this example. Figure 6 : is the particle size distribution diagram of the Fe3O4@SiO2@PEI magnetic nanoparticles synthesized in this example, the particle size is 11.98nm, and the coefficient of variation is 5.81%.
[0038] Embodiment 2:
[0039] 1. Preparation of oil-soluble Fe3O4 magnetic nanoparticles by high temperature thermal decomposition
[0040] Take 4.5g of solid ferric acetylacetonate, add 25.3g of toluene, 4.0g of oleic acid, and 4.5g of oleylamine, stir for half an hour under a nitrogen atmosphere, then quickly heat to 270°C and reflux for 2h. Collect the product and wash with ethanol until the upper layer is colorless and transparent to obtain oil-soluble Fe3O4 magnetic nanoparticles.
[0041] 2. Improve the dispersibility of Fe3O4 magnetic nanoparticles
[0042] Take 500 mg of the oil-soluble Fe3O4 magnetic nanoparticles obtained above and dissolve them in 5 mL of chloroform, add 50 mL of Tween-80 aqueous solution (1% w / v), heat to 90°C while stirring, and collect the liquid after opening for 1 hour, centrifuge several times with ethanol and deionized water, and disperse in 5 mL of deionized water to obtain an aqueous dispersion of Fe3O4 magnetic nanoparticles.
[0043] 3. Coating of Fe3O4 magnetic nanoparticles with silica shell
[0044] To the above-obtained dispersion, ethanol and deionized water were added in turn, with an alcohol-water ratio of 9:1. After stirring evenly, 1.5 mL of ammonia water was added and stirred at 20°C for half an hour. Then 1 mL of tetraethyl orthosilicate was added in five times with an interval of 10 min. After stirring for 12 h, the product was collected and washed by centrifugation with ethanol and deionized water at a low speed (1000 rpm) until there were no white particles. It was then dispersed in 5 mL of ethanol to obtain an ethanol dispersion of Fe3O4@SiO2 magnetic nanoparticles.
[0045] 4. Modification of the surface of Fe3O4@SiO2 magnetic nanoparticles with polyacetimide
[0046] Take 5 mL of the ethanol dispersion of the above-mentioned Fe3O4@SiO2 magnetic nanoparticles, add 5 mL of ethanol solution of polyacetimide (3% w / v), stir until mixed evenly, heat to 80°C and add 50 mL of aqueous solution of glutaraldehyde (3% w / v), continue to reflux for 1 hour after all the addition, wash the mixture with ethanol and water by centrifugation until the upper liquid is colorless and transparent, evaporate the liquid and disperse it in water.
[0047] Embodiment 3:
[0048] 1. Preparation of oil-soluble Fe3O4 magnetic nanoparticles by high temperature thermal decomposition
[0049] Take 2.3g of pentacarbonyl iron solid, add 37.9g of diethylene glycol and 1.4g of oleylamine, stir for half an hour under nitrogen atmosphere, then quickly heat to 240℃ and reflux for 1h. Collect the product and wash it with n-hexane and ethanol several times to obtain oil-soluble Fe3O4 magnetic nanoparticles.
[0050] 2. Improve the dispersibility of Fe3O4 magnetic nanoparticles
[0051] Take 500 mg of the oil-soluble Fe3O4 magnetic nanoparticles obtained above and dissolve them in 5 mL of tetrahydrofuran, add 100 mL of an aqueous solution of sodium dodecylbenzenesulfonate (2.5% w / v) and 50 mL of an aqueous solution of Tween-80 (1% w / v). Heat to 80°C while stirring, and collect the liquid after opening for 1 hour. Centrifuge several times with ethanol and deionized water, and then disperse in 5 mL of deionized water to obtain an aqueous dispersion of Fe3O4 magnetic nanoparticles.
[0052] 3. Coating of Fe3O4 magnetic nanoparticles with silica shell
[0053] Take 250 mL of ethanol and 5 mL of deionized water, add the obtained dispersion with stirring, add 7.5 mL of ammonia water, add 1.5 mL of tetraethyl orthosilicate, stir for 12 hours, collect the obtained product, wash it by centrifugation with ethanol and deionized water until the upper layer is colorless and transparent, and then disperse it in 5 mL of isopropanol to obtain an isopropanol dispersion of Fe3O4@SiO2 magnetic nanoparticles.
[0054] 4. Modification of the surface of Fe3O4@SiO2 magnetic nanoparticles with polyacetimide
[0055] Take 5 mL of the above-mentioned isopropanol dispersion of Fe3O4@SiO2 magnetic nanoparticles, add 25 mL of isopropanol solution of polyimide (3% w / v), heat to 70°C and then drop 50 mL of aqueous solution of glutaraldehyde (3% w / v), then continue to reflux for 1 hour, wash the mixture with ethanol by centrifugation until the upper liquid is colorless and transparent, evaporate the liquid and disperse it in water.
[0056] Comparative Example:
[0057] Take 500mg of the oil-soluble Fe3O4 magnetic nanoparticles synthesized in Example 1, add 5mL of tetrahydrofuran, ultrasonically disperse evenly and mechanically stir, and pass into nitrogen. Add 250mL of ethanol, 5mL of deionized water, mechanically stir in an ice-water bath, add ammonia water to adjust the pH value of the system to between 8-9, stir for half an hour, add 0.5mL of tetraethyl orthosilicate, stir for 2h, then add 0.5mL of tetraethyl orthosilicate, stir at room temperature for 12h and collect the resulting product, now find that the reaction system liquid surface floats with black globular solid, and there is milky white solid at the bottom. The black solid floating on the liquid surface is oil-soluble Fe3O4 magnetic nanoparticles, and the milky white solid at the bottom is the tetraethyl orthosilicate hydrolyzate. Oil-soluble Fe3O4 magnetic nanoparticles are not coated with SiO2 shell.
[0058] On the contrary, in embodiment 1, oil-soluble magnetic nanoparticles are treated with surfactant, and are changed from hydrophobicity to hydrophilicity, thereby easily coating SiO2 shell on its surface.SiO2, as an excellent inorganic surface modifier for magnetic nanoparticles, has the advantages of improving biocompatibility, dispersibility, hydrophilicity of magnetic nanoparticles.And because it itself has a stronger negative charge, it is easy to further modify the subsequent groups.SiO2 surface has a stronger negative charge, and the mode of electrostatic adsorption can be adopted to modify polyimide again, and the surface of the magnetic nanoparticle group after the surface modification has a large amount of amino groups, and good dispersibility in water.
[0059] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing polyacetimide magnetic nanoparticles having a core-shell structure, characterized in that: The magnetic nanoparticles have Fe3O4 as the core, SiO2 as the shell, and the shell surface modification material is polyacetimide; The preparation method comprises: Synthesizing oil-soluble magnetic nanoparticles by thermal decomposition method, comprising: dissolving an iron precursor in a high boiling point solvent, then adding a high boiling point reducing agent, removing a low boiling point solvent at 110-150°C and in a nitrogen atmosphere, then heating to a set temperature and refluxing to obtain oil-soluble magnetic nanoparticles; the iron precursor is one or more of pentacarbonyl iron, ferrous acetylacetonate, and ferrous oleate; the high boiling point solvent is one or more of toluene, eicosane, n-octadecane, and octadecene; the high boiling point reducing agent is one or two of oleic acid and oleylamine; the reflux temperature is 220-330°C, the reflux time is 0.5-2h, and the molar ratio of the iron precursor, the high boiling point solvent, and the high boiling point reducing agent is 1:(10-80):(1-9); The synthesized oil-soluble magnetic nanoparticles are treated with a surfactant to obtain magnetic nanoparticles dispersed in water. Specifically, the prepared oil-soluble magnetic nanoparticles are dissolved in a polar solvent, and an aqueous solution of a surfactant with a mass fraction of 0.5%-5% is added thereto, the temperature is controlled between 60-90° C., and the polar solvent is dried by stirring under a nitrogen atmosphere to obtain magnetic nanoparticles dispersed in water; the aqueous surfactant solution is one or more of an aqueous solution of sodium dodecylbenzenesulfonate, an aqueous solution of sodium dodecyl sulfate, and an aqueous solution of Tween; The surface of the obtained magnetic nanoparticles dispersed in water is coated with a SiO2 shell layer to obtain Fe3O4@SiO2 magnetic nanoparticles dispersed in water. Specifically, the magnetic nanoparticles dispersed in water are taken, ethanol is added to control the volume of ethanol to be between 8 and 12 times of water, and then ammonia water is added to adjust the pH of the system to alkaline, and tetraethyl orthosilicate is added. After reaction at 0-20°C, the mixture is washed and dispersed in an alcohol solution to obtain an alcohol dispersion of Fe3O4@SiO2 magnetic nanoparticles; An alcohol solution containing poly(acetimide) was added to Fe3O4@SiO2 magnetic nanoparticles to react and obtain Fe3O4@SiO2@PEI magnetic nanoparticles.
2. The method for preparing polyacetimide magnetic nanoparticles having a core-shell structure according to claim 1, characterized in that: The polar solvent includes one or more of trifluoroacetic acid, dimethyl sulfoxide, N,N-dimethylformamide, pyridine, acetone, tetrahydrofuran, and chloroform; the mass ratio of the oil-soluble magnetic nanoparticles, the polar solvent, and the surfactant aqueous solution is 1: (10-30): (200-400).
3. The method for preparing polyacetimide magnetic nanoparticles having a core-shell structure according to claim 1, characterized in that: The alcohol solution includes one or more of methanol, ethanol, n-butanol and isopropanol. The volume ratio of the magnetic nanoparticles dispersed in water to tetraethyl orthosilicate is 1:(0.03-0.1).
4. The method for preparing polyacetimide magnetic nanoparticles having a core-shell structure according to claim 1, characterized in that: The mass fraction of the Fe3O4@SiO2 magnetic nanoparticles dispersed in water is 0.4%-4%, the mass fraction of polyacetimide in the alcohol solution containing polyacetimide is 0.1%-1%, and then an aldehyde solvent with a mass fraction of 1%-10% is added dropwise, refluxed at 60-90°C for 1-4h, and Fe3O4@SiO2@PEI magnetic nanoparticles are obtained after washing.
5. The method for preparing polyacetimide magnetic nanoparticles having a core-shell structure according to claim 4, characterized in that: The alcohol solution in the alcohol solution containing polyacetimide includes one or more of methanol, ethanol, n-butanol, and isopropanol; the aldehydes are one or more of formaldehyde, acetaldehyde, succinaldehyde, and glutaraldehyde; the volume ratio of the Fe3O4@SiO2 magnetic nanoparticles dispersed in water, the alcohol solution containing polyacetimide, and the aldehyde solvent is 1: (0.1-0.3): (10-30).
Citation Information
Patent Citations
Fe3O4 nano-particles with high dispersion stability in water phase, and preparation method thereof
CN102815753A
Core-shell type nanometer composite material, and preparation method and applications thereof
CN108786760A